A Comparative Study on Internet Addiction in Iranian People With and Without Acne Vulgaris - Ali Pourramzani; Amir Mohammad Alinejad; Fatemeh Eslamdoust-Siahestalkhi; Kaveh Gharaei Nejad (Journal of Holistic Nursing and Midwifery)
Introduction: Acne vulgaris is a skin disorder that affects the mental health and social relationships of individuals. Objective: In this study, we aim to compare internet addiction between people with acne vulgaris (PwAV) and non-acne people. Materials and Methods: This comparative/analytical study was performed on 114 PwAV referred to a dermatology clinic and 114 people without acne in Rasht, northern Iran. A demographic form and internet addiction test (IAT) were used to collect data. Chi-square test, independent t-test, and analysis of variance were used for statistical analysis. P<0.05 was considered statistically significant. Results: The mean age of PwAV and non-acne groups was 26.6±5.56 and 27.53±4.71 years, respectively. Regarding the severity of acne, 65.5% of patients had mild acne, 30.9% moderate acne, and only 3.6% had severe symptoms. The IAT score was significantly higher in the PwAV group than in the non-acne group (P=0.01). In terms of severity, most individuals in both groups had a mild level of internet addiction, and there was no significant difference between the two groups. The hours of internet use per day were higher in the PwAV group than in the non-acne group, but the difference was not significant. In both groups, the IAT score was significantly higher in people <26 years of age (P=0.02 for PwAV; P=0.02 for non-acne group) and single people (P=0.01 for PwAV; P=0.03 for non-acne people) Conclusion: Internet addiction is higher in Iranian PwAV, but its severity is not significantly different between people with and without acne vulgaris. Young and single people (with or without acne vulgaris) have higher internet addiction.